Penerapan ISO 31000 dalam Manajemen Risiko Pada Industri Retail: Studi Kasus Toko Sembako Madina - Amelia Rahmadani; Indy Fauziah Hanifa; Lailafitri Pratiwi Kadmadi; Putri Dewi Renggani; Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study aims to analyze the implementation of ISO 31000 in risk management at Toko Sembako Madina, a retail business engaged in the sale of staple foods and daily necessities. Effective risk management is very important for the retail industry, especially in facing the uncertainties and complications of today's business world. This study uses a case study method with a qualitative approach, collecting data through interviews, observations, and document analysis. The results show that Toko Sembako Madina faces several major risks in running its business, namely fierce competition, theft and counterfeit money, employee involvement in fraud, and limited capital. This study provides recommendations to improve the effectiveness of risk management atToko Sembako Madina, including the development of a more comprehensive risk management system, increased employee awareness and training, and the use of digital technology for the sustainability of Toko Sembako Madina.